Ecological genetics - Real, Leslie (Princeton University Press, 2017)
This volume represents work by five distinguished ecological geneticists, offering an up-to-date source for theoretical concepts and experiments in an exciting field. Combining ecological fieldwork and laboratory genetics, ecological genetics examines the adjustments and adaptations of wild populations to their environments. Articles focus on important interactions between genetics and population ecology, delving into issues like gene flow and migration, population differentiation, the maintenance of genetic variation, and the demographic and spatial structure of populations. The contributors--Janis Antonovics, Michael Lynch, Montgomery Slatkin, Joseph Travis, and Sara Via--emphasize the importance of population size and structure, interaction between local selection and genetic drift, and an expanded phenotype including quantitative as well as qualitative characters. This new form of ecological genetics focuses on large-scale geographic variation in demographic and genetic dynamics among small, partially isolated populations and will prove extremely valuable in natural resource management and in rare or endangered species conservation. Originally published in 1994. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.
Keywords: Ecological genetics.; Evolution (Biology); Population genetics.; Ecology.; Genetics, Population; Biological Evolution; Ecology; Génétique écologique.; Génétique des populations.; Évolution (Biologie); Écologie.; evolution.; ecology.; SCIENCE -- Life Sciences -- Biology.; Ecological genetics; Population genetics; Populatiegenetica.; Ecologie.; Evolutie.; Évolution (biologie); Electronic books.